2002
DOI: 10.1046/j.1467-2494.2002.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Nudging hair shedding by antidandruff shampoos. A comparison of 1% ketoconazole, 1% piroctone olamine and 1% zinc pyrithione formulations

Abstract: Hair shedding and hair thinning have been reported to be affected by dandruff and seborrhoeic dermatitis. The present study was conducted in 150 men presenting with telogen effluvium related to androgenic alopecia associated with dandruff. They were randomly allocated to three groups receiving each one of the three shampoos in the market containing either 1% ketoconazole (KTZ), 1% piroctone olamine (PTO) or 1% zinc pyrithione (ZPT). Shampoos had to be used 2-3 times a week for 6 months. Hair shedding during sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…The complex interactions between hair growth, sebaceous gland functions, angiogenesis [69,70], micro-inflammation and its counterpart immuno-suppression [51][52][53][54][55][56][57] and neuroendocrine influences [41,71] are incompletely characterized. The environmental impact including solar irradiation [49,50] and commensal microorganisms [56,59,72,73] cannot be neglected either.…”
Section: Effluviummentioning
confidence: 99%
See 1 more Smart Citation
“…The complex interactions between hair growth, sebaceous gland functions, angiogenesis [69,70], micro-inflammation and its counterpart immuno-suppression [51][52][53][54][55][56][57] and neuroendocrine influences [41,71] are incompletely characterized. The environmental impact including solar irradiation [49,50] and commensal microorganisms [56,59,72,73] cannot be neglected either.…”
Section: Effluviummentioning
confidence: 99%
“…Placing a piece of nylon netting over the drain, will usually trap hairs lost during washing. An entire day collection should be placed in a clear envelope or sandwich bag [57,73,86]. The date and information on whether shampoo has been used should be recorded.…”
Section: Daily Hair Countsmentioning
confidence: 99%
“…There were positive results even with the most infrequent use of 2-3 times per week (Henry et al, 2003), suggesting that this may be an adequate regimen for the use of topical ketoconazole in the treatment of AGA. Of the reviewed studies, all supported the use of ketoconazole for the treatment of AGA in some regard.…”
Section: Discussionmentioning
confidence: 92%
“…Zinc pyrithione is known for its use in treating dandruff and seborrhoeic dermatitis. Recent studies of anti-dandruff shampoos containing zinc pyrithione have been reported to reduce hair loss [13,18]. Dexpanthenol (vit.…”
Section: Discussionmentioning
confidence: 99%